Effect of Flippeed Classroom Models and Creative Thinking of Science Literation Students - Susanti, Wiwi; Supena, Asep; Cahyana, Ucu (Universitas Negeri Semarang, 2020)
The flipped classroom model, which is often heard in recent years, is known as a new pedagogical approach in which traditional instruction is reversed. The study aims to determine the effect of the flipped classroom model and creative thinking on the scientific literacy of grade VI students of SDN Guntur 01, South Jakarta. This research uses a 2x2 factorial design. The research sample was divided into two treatment groups, namely the experimental class and the control class. The experimental class was given treatment by carrying out the learning model of the flipped classroom , while the control class was given treatment by carrying out the expository model learning. The results showed: (1) there was a difference in scientific literacy between the experimental class and the control class, with scientific literacy higher than the control class. (2) there is a difference in scientific literacy between groups of students with high levels of creative thinking in the experimental class [A 1 B 1 ] and the control class [A 2 B 1 ]. (3) there is a difference in scientific literacy between groups of students with low creative thinking levels in the experimental class [A 1 B 2 ] and the control class [A 2 B 2 ]. (4) there is an effect of interaction between learning models and creative thinking on scientific literacy. Purpose of the flipped classroom model is to use face to face time more effectively in the learning process. There are many definitions related to flipped classroom is a student-centred learning method consisting of two parts with interactive learning activities during lesson and individual teaching based on computer out of lesson.